Mechanical and morphological properties of bio-phenolic/epoxy polymer blends - Ismail, Ahmad Safwan; Jawaid, Mohammad; Hamid, Norul Hisham; Yahaya, Ridwan; Hassan, Azman (MDPI AG, 2021)
Polymer blends is a well-established and suitable method to produced new polymeric materials as compared to synthesis of a new polymer. The combination of two different types of polymers will produce a new and unique material, which has the attribute of both polymers. The aim of this work is to analyze mechanical and morphological properties of bio-phenolic/epoxy polymer blends to find the best formulation for future study. Bio-phenolic/epoxy polymer blends were fabricated using the hand lay-up method at different loading of bio-phenolic (5 wt%, 10 wt%, 15 wt%, 20 wt%, and 25 wt%) in the epoxy matrix whereas neat bio-phenolic and epoxy samples were also fabricated for comparison. Results indicated that mechanical properties were improved for bio-phenolic/epoxy polymer blends compared to neat epoxy and phenolic. In addition, there is no sign of phase separation in polymer blends. The highest tensile, flexural, and impact strength was shown by P-20(biophenolic-20 wt% and Epoxy-80 wt%) whereas P-25 (biophenolic-25 wt% and Epoxy-75 wt%) has the highest tensile and flexural modulus. Based on the finding, it is concluded that P-20 shows better overall mechanical properties among the polymer blends. Based on this finding, the bio-phenolic/epoxy blend with 20 wt% will be used for further study on flax-reinforced bio-phenolic/epoxy polymer blends.